POSTMORTEM TOXICOLOGY ANALYSIS IN INDIA: RETHINKING THE FUTURE (Journal of Forensic Medicine & Toxicology, 2022)
In India, it is prevalent to collect and preserve samples for post-mortem toxicology analysis during autopsy in any unnatural death. Recent trends in poisoning show a change in the poisons used for suicidal or homicidal purposes as well as those causing accidental exposures. Newer developments in analytical technology and techniques have made it possible to detect poisons even from minute samples. However, despite these advances, there has been no change in the guidelines for sample collection during autopsies and the current practices are based on recommendations from decades ago. Contrary to practices prevalent in India, most developed nations have optimised their protocols for the collection of samples, storage, and analysis based on the latest technological advances.
Keywords: Autopsy; Forensic science laboratories; Guidelines; Protocol; Samples; Toxicology analysis